2016
DOI: 10.3390/e18080308
|View full text |Cite
|
Sign up to set email alerts
|

Soft Magnetic Properties of High-Entropy Fe-Co-Ni-Cr-Al-Si Thin Films

Abstract: Soft magnetic properties of Fe-Co-Ni-Al-Cr-Si thin films were studied. As-deposited Fe-Co-Ni-Al-Cr-Si nano-grained thin films showing no magnetic anisotropy were subjected to field-annealing at different temperatures to induce magnetic anisotropy. Optimized magnetic and electrical properties of Fe-Co-Ni-Al-Cr-Si films annealed at 200 • C are saturation magnetization 9.13 × 10 5 A/m, coercivity 79.6 A/m, out-of-plane uniaxial anisotropy field 1.59 × 10 3 A/m, and electrical resistivity 3.75 µΩ·m. Based on these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…magnetron sputtering [34][35][36], laser cladding [37,38], spraying [39], electrodeposition [40], plasma-transferred arc cladding [41], and others. The present experimental results have proved that HEA films and coatings can show excellent mechanical and physical properties, such as the high hardness and elastic modulus [42,43], superior wear resistance [44], corrosion [45] and temperature resistance [46], as well as the appealing electrical [47] and magnetic properties [48].…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…magnetron sputtering [34][35][36], laser cladding [37,38], spraying [39], electrodeposition [40], plasma-transferred arc cladding [41], and others. The present experimental results have proved that HEA films and coatings can show excellent mechanical and physical properties, such as the high hardness and elastic modulus [42,43], superior wear resistance [44], corrosion [45] and temperature resistance [46], as well as the appealing electrical [47] and magnetic properties [48].…”
Section: Introductionsupporting
confidence: 55%
“…Lin et al [48] fabricated the FeCoNiCrAlSi thin films and reported the excellent soft magnetic properties. The film had a simple BCC structure under as-deposited and post-annealing conditions at 400°C and below.…”
Section: Physical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wherein the hypereutectic CoCrFeNiNb 1.0 alloy coating with the highest hardness exhibited the best wear resistance under the same wear condition, the dry wear test showed the wear mass loss of CoCrFeNiNb 1.0 alloy coating was less than a third of the substrate. The high hardness and wear resistance properties were considered with the fine lamellar eutectic structure and proper combination of FCC and Laves phases.Crystals 2018, 8, 409 2 of 11 superconductivity [24,25], soft magnetism [26,27], etc. As a result, HEAs can be an attractive material for a range of applications.…”
mentioning
confidence: 99%
“…Crystals 2018, 8, 409 2 of 11 superconductivity [24,25], soft magnetism [26,27], etc. As a result, HEAs can be an attractive material for a range of applications.…”
mentioning
confidence: 99%